Phytal Proteins Of Jackfruit (Artocarpus Heterophyllus Lam.) And Their Immuno-Compatibility Assessment With Indoor Fungal Antigens And Human Antibody (Applied Biological Research, 2020)
Several phytal extracts in Ayurveda are used in controlling certain  allergies and bronchial disorders. In present study, the suspected  anti-allergic activity of a tropical perennial tree, jackfruit (Artocarpus  heterophyllus Lam), roots were evaluated against allergens that cause  bronchial allergy/asthma. The chemical composition of phytal  extracts indicated the presence of alkaloids, flavonoids, phytosterols,  etc. with suspected anti-allergic capabilities. The binding capabilities  between extracts, indoor fungal antigens and human antibodies (Ig E) based on different immunoassays indicated that jackfruit root protein of 75 kDa can be considered as possible and novel treatment option for common respiratory allergies.
Keywords: Allergens; jackfruit; immuno-binding; phytochemicals